Boundary-crossing learning in agricultural learning systems: formative interventions for water and seed provision in southern Africa - Pesanayi, Victor Tichaona (Rhodes University, Faculty of Education, Department of Education, 2019)
This research was conducted in the Amathole rural district of the Eastern Cape Province of South Africa, and in Zvishavane and Zhombe rural districts of the Midlands Province of Zimbabwe over a period of four years. In the first two years of this period I was involved in co-engaged boundary-crossing expansive learning processes with research participants from agricultural education (agricultural college lecturers, principals and university lecturers), extension services (extension officers, advisors and workers), small-scale farmers and a local economic development (LED) agency as agricultural learning activity systems. The latter was applicable only to the South African nested case while the rest applied to both country nested cases. The study focusses on the boundary-crossing learning of sustainable agricultural water relevant for small-scale farming contexts under rain-fed and climate constrained conditions with specific attention to rainwater harvesting and conservation and climate-adaptive seed. The study employed cultural-historical activity theory (CHAT) and developmental work research methodology developed by Yrjö Engeström and his colleagues at the Centre for Researching Activity Development and Learning (CRADLE) at the University of Helsinki in Finland. The study was guided by three objectives. The first objective was to find out how the different groups represented across the activity systems listed above learn together to mediate and communicate sustainable agricultural water and seed saving. To address this objective I conducted focus groups and interviews with key informants, made observations and analysed documents. The second objective was to explore and document the socio-ecological histories of rainwater harvesting and conservation, locally-adaptive seed systems and associated value chains, and socio-cultural histories of agricultural learning systems in the context of small-scale farming using historical and ethnographic research techniques. The third objective was to understand how learning, curriculum innovation and mediation tools for agricultural extension education and farmer training that can expand learning of rainwater harvesting and conservation sustainable practices for improved local agricultural water and climate-adaptive non-formal seed systems in agricultural education and small-scale farmer activity systems could be co-generated. This third objective constituted the boundary-crossing expansive learning that emerged from change laboratory workshops carefully designed to explore the common water for food object across the different but related activity systems. The study reveals historically-persisting tensions and contradictions in the work of agricultural college lecturers, small-scale farmers and extension workers that limit their ability to work together relationally leaving them operating in isolated 'silos'. The industrially-driven agricultural college curriculum promoting conventional irrigated agriculture conflicted with the college's objective of producing extension workers who will work with resource-poor small-scale farmers in rain-fed farming systems. This conflict was aggravated by the work of extension workers who had little to no knowledge regarding how to support small-scale farmers facing persistent drought and consequent crop failure due to poor and erratic rainfall. At the same time extension services promoting genetically modified (GMO) seed in South Africa were in conflict with some small-scale farmers' demands for seed that was adapted to their changing climate and their ability to operate independently with access to and ownership of land. This study shows that the work of agricultural colleges and extension services often defeats its intended structural objectives due to historically-constituted power relations around knowledge. This study has demonstrated the effectiveness of co-generative formative interventions in boundary-crossing scenarios in learning network contexts for expansion of activity in farming communities, agricultural colleges and extension services, with emphasis of transformed activity towards engaging a collective object of rainwater harvesting and conservation for more sustainable agriculture and poverty alleviation. The study shows that diverse combinations of change practice courses, change laboratories, demonstration sites and media engagements as mediation processes in the context of learning networks strengthened the possibility for boundary-crossing expansive learning across activity systems of agricultural college lecturers, smallholder farmers, extension workers and local economic development agency facilitators. Three of the five mediation processes emerged out of the formative intervention processes in both the South African and Zimbabwean case studies while two were not realised in the Zimbabwean case study, namely the change practice course and media engagements, due to different formative intervention conditions, inadequate time and resources. Boundary-crossing was enabled by a variety of actions including understanding and identifying with the context of the other (i.e. developing empathy) as a result of change laboratory workshops that also ensured confrontation with relational contradictions. The study concludes that it is possible for historically-constituted contradictions around water for food to be resolved when participants from different agricultural learning systems co-engage as equals in boundary-crossing change laboratory fora mediated by appropriate tools and processes. The study contributes to innovation in agricultural learning systems in southern Africa, in particular to means of engaging across boundaries of previously largely disconnected activity systems in ways that benefit smallholder farmers who have previously been marginalised from mainstream agricultural learning systems.
Keywords: Agriultural extension work -- Africa, Southern; Agriultural colleges -- Africa, Southern; Farmers -- Education -- Africa, Southern; Agriculture and state -- Africa, Southern; Sustainable agriculture -- Africa, Southern